To the 50th Anniversary of the European Patent Convention (1973–2023) - R. A. Kasyanov; I. M. Yazberdiev (Московский журнал международного права, 2024)
INTRODUCTION. This paper reflects historical overview of long-standing emergence of mechanisms of judicial protections of patent rights conferred by European patens which begun even in 1950-s and ended with start of operations of the Unified Patent Court in 2023. The paper demonstrates that the establishment of the similar mechanism within the Eurasian Patent Organization or Eurasian Economic Union may require different approaches because of possible centralization of industrial property protection under Eurasian Patent Organization.METHODS AND MATERIALS. The research materials for this paper are scientific works of foreign and Russian scientists and officials of the European Patent Office and the Eurasian Patent Office, legal acts of international and regional levels and drafts thereof. Methodological basis of this research are general and special scientific methods.RESEARCH RESULTS. This paper suggests periodization in emergence and evolution of dispute resolution mechanisms for European patents, reveals rationales for establishment of the unified patent judiciary in Europe and outlines directions for further research of prospects of creation of the similar mechanism in the Eurasian region. Some findings made in this article may facilitate the growth of such researches.DISCUSSION AND CONCLUSIONS. European Union (EU) accumulated broad experience in establishment of the dispute resolution mechanisms for European patents. Due to uniqueness the Unified Patent Court is of great interest when researching prospect of improvements of the patent judiciary and quasi-judicial mechanisms under the Eurasian Patent Convention. However, trends of developments of the Eurasian Patent Organization and possible centralization of the regional protection of industrial property may testify that a Eurasian analogue of the Unified Patent Court would have a different institutional form.